The social construction of reality: the role of professionals in the thematic agenda building - Cáceres Zapatero, María Dolores (Estudios sobre el Mensaje Periodístico, 2012)
This paper presents the results of a Delphi study, as part of a wider investigation, whose mind is to analyze the discourse of social communication that become the subject of the news agenda, and de foundations on which this discourse becomes hegemonic, about “truth” and “communication”. This article discusses how the production practices of journalism and professional routines affect the construction of hegemonic discourses in society, from the voice of their own producers: journalists of sources and journalists of media This raises one hand, the flow of information between the sources and media and, second, habits and attitudes that compromise this traffic.
Keywords: agenda building; newsmaking; newspaper routines; production of news.